2018
DOI: 10.1103/physrevd.98.014014
|View full text |Cite
|
Sign up to set email alerts
|

DΞ and D*Ξ molecular states from one boson exchange

Abstract: We explore the existence of DΞ and D Ã Ξ molecular states within the one boson exchange model. We regularize the potential derived in this model with a form factor and a cutoff of the order of 1 GeV. To determine the cutoff, we use the condition that the Xð3872Þ is reproduced as a pole in the J PC ¼ 1 þþ D ÃD amplitude. From this, we find that the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 85 publications
(118 reference statements)
1
21
0
Order By: Relevance
“…We notice that form factors of a higher polarity prefer larger values of Λ: for a monopolar form factor the ideal cutoff is in the vicinity of Λ ≃ 1 GeV, while for a dipolar Λ ≃ 1.5 GeV 3. In a previous work[55] we obtained Λ = 1.04 +0 18. −0.10 GeV, which is a bit higher.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…We notice that form factors of a higher polarity prefer larger values of Λ: for a monopolar form factor the ideal cutoff is in the vicinity of Λ ≃ 1 GeV, while for a dipolar Λ ≃ 1.5 GeV 3. In a previous work[55] we obtained Λ = 1.04 +0 18. −0.10 GeV, which is a bit higher.…”
mentioning
confidence: 60%
“…−0.10 GeV, which is a bit higher. The reason for the difference is that in Ref [55]. the effective pion mass for the one pion exchange piece of the OBE potential was taken to be µ π = 138 MeV instead of µ π = 0.…”
mentioning
confidence: 99%
“…Starting from early quark models [1], work along this line has been rather extensive and fruitful [2][3][4][5][6][7][8]. QCD lattice has also contributed to this area [9][10][11] and dynamical models building molecular states in coupled meson-baryon channels [12][13][14][15][16][17][18][19][20][21][22][23][24] have also brought their share to this intense research. There are also many review papers on the subject to which we refer the reader [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…[13]. These studies are often based on the phenomenological meson-exchange models [14][15][16][17]. Several studies considered compact diquark-diquark-antiquark internal structure and found P c , e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%